Peran Petugas Pembina Dalam Pengendalian Perilaku Merokok Pada Narapidana Di Lapas Kelas I Makassar - Fauziah Nur Masyurah; Yusriani; Andi Mansur Sulolipu; Rizki Amelia AP; Nurfardiansyah Burhanuddin (Window of Public Health Journal, 2026)
Smoking habits at the Makassar Class I Penitentiary (Lapas) remain a challenge to implementing the Smoke-Free Area (KTR) policy. This condition indicates the need for effective communication strategies from correctional officers to support the control of inmates' smoking behavior. This study aims to examine the role and communication strategies of correctional officers in controlling inmates' smoking behavior in Makassar Class I Penitentiary. This study employed a qualitative, exploratory design and was conducted in February–March 2026. The research informants consisted of four correctional officers, six inmates, and one health worker, all purposively selected. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the stages of data reduction, data presentation, and conclusion drawing. The results showed that correctional officers served as educators, facilitators, and role models in implementing guidance. The communication strategies implemented included persuasive interpersonal communication, group communication, and simple educational media. This strategy was perceived as being able to increase inmates' awareness to reduce smoking habits; however, behavioral changes have not been optimal due to obstacles such as weak enforcement of the Smoke-Free Area policy and the circulation of illegal cigarettes within the prison. This study concludes that effective control of smoking behavior requires a sustainable communication strategy, strengthened implementation of Smoke-Free Area policies, and a conducive environment.